Magnetic separation of apoptotic cells with lectin‐conjugated microparticles: Magnetische Abtrennung apoptotischer Zellen mit Lektin‐konjugierten Mikropartikeln. Issue 2 (2nd February 2016) - Tomin, A.; Dumych, T.; Kril, I.; Antonyuk, V.; Chopyak, V.; Munoz, L.; Stoika, R.; Herrmann, M.; Bilyy, R.
Abstract : Both phosphatidylserine (PS) and oligomannose/desialylated glycans are known to be exposed on the surface of dying cells and used by macrophages to endure effective efferocytosis. Recognition of phosphatidylserine by annexin A5 is widely implicated in various technologies aimed to isolate apoptotic cells. Our recent finding suggested that recognition of phosphatidylserine and apoptotic glycans by macrophages is of complementary nature. Here we developed lectin‐conjugated magnetic microparticles recognizing specific glycans of apoptotic cells and its use for detection and separation of dying cells. We conjugated Narcissus poeticus lectin, specific to oligomannose N‐glycans, and Viscum album agglutinin, specific to desialylated glycans to the surface of superparamagnetic and fluorescent‐superparamagnetic microparticles, and tracked their binding to subpopulations of human polymorphonuclear leukocytes undergoing apoptosis. Glycan targeting microparticles were effectively found on apoptotic cells, while specific lectin inhibitors of carbohydrate nature (like heptylmannoside), displaced dying cells from complexes with microparticles, suggesting a reversible binding. Simultaneous application of microparticles conjugated with annexin A5 and Viscum album agglutinin exhibited additive effect on the efficiency of apoptotic cells removal from population.